Hubungan Kualitas Tidur dengan Siklus Menstruasi Pada Mahasiswi Tingkat Akhir Fakultas Keperawatan : The Relationship Between Sleep Quality and Menstrual Cycles Among Final-Year Nursing Students - Wedya Wahyu; Lili Fajria; Filliya Azzura (Fakultas Keperawatan Universitas Andalas, 2024)
Menstrual cycle disorders are caused by various problems, one of which is sleep quality. Poor sleep quality tends to be experienced by final-year students. One of the effects of poor sleep quality is menstrual cycle disorders. This study aims to determine the relationship between sleep quality and menstrual cycle in final year students of program A 2018 Faculty of Nursing, Andalas University. This type of research is descriptive-analytic with a cross-sectional design. The sample in this study amounted to 75 people with the purposive sampling method. The instrument used was the Pittsburgh Sleep Quality Index (PSQI) which was calculated for 3 consecutive months and the menstrual cycle questionnaire was calculated for consecutive cycles. Data analysis using chi-Square test. The results of this study showed that the frequency distribution of sleep quality obtained the highest results (62.7%) in the poor category and the menstrual cycle resulted in more than half (54.7%) having irregular cycles, with a p-value = 0.000 (p < 0.05) which means that there is a significant relationship between sleep quality and menstrual cycle in final year students of program A 2018 Faculty of Nursing, Andalas University. Based on this, it is suggested that respondents be able to manage time during the day so that they can rest comfortably at night.